In vitro culture technique of Camellia sinensis L for epicatechin production with phosphor inducer - Sutini Sutini; Widiwurjani Widiwurjani; Nora Augustien; Hadi Suhardjono; Guniarti Guniarti; Djoko Agus Purwanto; Wirdhatul Muslihatin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
In several ASEAN countries, in vitro culture techniques are one of the cultivation technologies that applied in sustainable agriculture. This technology has been performed in response to obtain the secondary metabolite of epicatechin from Camellia sinensis L. However, The yield of epicatechin is remaining low than in the field production. To overcome this problem, phosphor inducers is desirable to be supplemented in the study. The young leaf shoots of C. sinensis L was sliced on a culture-filled bottle, the sliced part was re-cultivated in the same medium by supplementing of 2,4-D growth regulators, then the medium was optimized by phosphor inducer with range of concentartions 40-200 ppm. The callus formation was then evaluated using high performance liquid chromatography methods to obtain qualitative and quantitative data. The results showed that the yield of epicatechin was obtained to 11.75%, suggesting that the supplementing of phosphor inducers at cultivation of in vitro culture of C. sinensis L able to improve the production of epicatechin by in vitro culture technique.